Transcriptional activity of transposable elements may contribute to gene expression changes in the syncytium formed by cyst nematode in arabidopsis roots. (2nd September 2017) - Piya, Sarbottam; Bennett, Morgan; Rambani, Aditi; Hewezi, Tarek
ABSTRACT: Transposable elements (TEs) are mobile genetic materials that constitute a large fraction of plant genomes. Recent experimental evidences indicate that TEs can play key regulatory roles in controlling the expression of adjacent genes during plant development and stress responses. Nevertheless, information about the transcriptional activity of TEs and their impact on proximal genes during plant-nematode interaction remains largely unknown. Here, we identify of differentially expressed TEs and report their possible influence on the expression of nearby genes during the susceptible interaction between the beet cyst nematode Heterodera schachtii and Arabidopsis thaliana . Analysis of our RNA-seq data of H. schachtii –infected roots, and the corresponding non-infected controls, resulted in the identification of 99 and 93 differentially expressed TEs at 5 and 10 d post infection, respectively. More than 2-thirds of these TEs were activated, suggesting that H. schachtii infection induces TE activation to a much greater degree than repression. Remarkably, the majority of these TEs were located within 2 kb of protein-coding genes, many of these genes were previously found to change expression in the H. schachtii –induced feeding sites. Taken together, our analysis provides novel insight into a possible role of actively transcribed TEs in the regulation of gene transcription in the nematode feeding sites during H. schachtii parasitism of Arabidopsis.